2009
DOI: 10.1292/jvms.001279
|View full text |Cite
|
Sign up to set email alerts
|

Relative Nerve Blocking Properties of Bupivacaine and Ropivacaine in Dogs Undergoing Brachial Plexus Block Using a Nerve Stimulator

Abstract: ABSTRACT. In the present study, the efficacy of a nerve stimulator in performing brachial plexus block (BPB) in dogs was investigated. The nerve blocking effects of bupivacaine and ropivacaine for BPB were also compared. Twelve beagles were allocated to groups based on the following treatments: conventional BPB with 0.5% bupivacaine (0.5% BupiM group) or BPB with 0.5% bupivacaine, 0.5% ropivacaine or 0.75% ropivacaine and a nerve stimulator (the 0.5% BupiS, 0.5% RopiS and 0.75% RopiS groups, respectively). Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The success rate for full brachial plexus blockade in this study was approximately 86%, similar to that reported in dogs (75%) and goats (95%) (Moens ; Sakonju et al. ). The success rate of blind infiltration of local anaesthetic was only 20% in goats (Moens ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The success rate for full brachial plexus blockade in this study was approximately 86%, similar to that reported in dogs (75%) and goats (95%) (Moens ; Sakonju et al. ). The success rate of blind infiltration of local anaesthetic was only 20% in goats (Moens ).…”
Section: Discussionsupporting
confidence: 89%
“…Brachial plexus block can be achieved by injecting a local anaesthetic agent around the brachial plexus nerves at the approximate level of the scapulohu-meral joint. A peripheral nerve stimulator can be used to locate accurately the radial, median, ulnar, musculocutaneous and axillary nerves (Skarda & Tranquilli 2007a), and this technique enhances the chances of successful BPB in small animals and may allow a reduction in the dose of local anaesthetic agent (Futema et al 2002;Wenger et al 2005;Mahler & Reece 2007;Sakonju et al 2009;Mosing et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This was similar to the study by D Tripathi et al, Modak S Basantwani S, Anupreet Kaur et al and Iwao Sakonju et al, which reported shorter duration of action with Ropivacaine. [14][15][16]19 However, it is in contrast to the study by Himat Vaghadia et al, which found that both drugs were comparable in duration of action. 20 However, in this study, different concentrations of the anesthetic agents were used, which might have led to the comparable results.…”
Section: Discussionmentioning
confidence: 90%
“…Absence of autonomic cardiopulmonary reactions to the surgical manipulation may be attributed to the efficacy of brachial plexus block. Apart from lidocaine, other local anaesthetics can be used; bupivacaine has been shown to confer long term perioperative analgesia while rupivacaine provides superior analgesia with minimal motor effects [ 18 ] owing to the fact that it is less potent at blocking Aβ fibres, but more potent in blocking Aδ and C fibres [ 19 ].…”
Section: Discussionmentioning
confidence: 99%